Employer Branding Literature Review - Singh, Rajesh Prettypal (Feedforward: Journal of Human Resource, 2021)
The concept of employer branding has attracted many researchers’ attention in the recent years. In today’s business environment, employer branding becomes one important source of competitive advantage that creates value for all companies. Organizations have identified employer branding as an important tool for attracting and retaining a talented workforce. The aim of this study is to get an understanding of employer branding on a broader spectrum and to examine employee engagement, employee retention, and employee satisfaction as the outcomes of employer branding. The paper focused by clarifying the definitions and the outcomes of employer branding.